A Natural Dye in a Mesophase Region of Cetyltrimethylammonium Bromide/ Octan-l-ol/Water System - Suhaimi, Hamdan; Ahmad, Faujan; Desa, Mohd Zaizi; Che Rose, Laili (Universiti Putra Malaysia Press, 1997)
A naturally occurring dye, curcumin, was added to a series of lamellar liquidcrystal mesophases consisting of cetyltrimethylammonium bromide (CTAB),octan-1-o1 and water at 30°C. The changes brought about by the addition of the natural dye were followed by optical microscopy and small angle X-ray diffraction techniques. The inter layer spacings of the lamellar liquid crystal mesophases with the natural dye were observed to be lower than the corresponding structure without dye at the equivalent volume ratio of water. The effect of water and the hydrocarbon chain of the lamellar liquid crystal structure were found to be minimal and further inclusion of curcumin prevented the formation of the mesophase